KEPERCAYAAN TRADISIONAL, PRAKTIK BUDAYA, POLA PENGAMBILAN KEPUTUSAN PADA IBU HAMIL DI PEDESAAN DAN PERKOTAAN INDONESIA - Maryuni Maryuni; Legina Anggraeni; Luthfi Handayani; Irwanti Gustina (JURNAL KESEHATAN REPRODUKSI, 2024)
Traditional Beliefs, Cultural Practices, Decision-Making Patterns In Pregnant Women In Rural And Urban Indonesia Background: Maternal mortality is a major public health problem in developing countries including Indonesia. Maternal mortality is heavily influenced by traditional beliefs and cultural practices during pregnancy. Objective: To investigate how traditional beliefs, cultural practices, and decision-making patterns in pregnant women in rural and urban areas in Indonesia. Method: Qualitative design research of phenomenology. The study was conducted in rural and urban areas of Indonesia, from July to November 2023. The main informants were 20 pregnant women, 2 key informants for community midwives, and 2 health cadres. Sample selection using purposive sampling. Data collection with observation and in-depth interviews. Data analysis using content analysis. Results: Pregnant women in both regions still adhere to pregnancy-related beliefs such as 7-month ceremonies and carrying bangles when traveling. Cultural practices during pregnancy, there are still pregnant women who do food abstinence, such as pineapple, durian, papaya, and meat. The pattern of decision-making for pregnant women in urban areas is carried out with the husband, in rural areas by extended families. Conclusion: There are still negative traditional beliefs and cultural practices of pregnant women so this study can be used as a basis for further research development for rural and urban communities in Indonesia.